Association of Maternal Mild Hypothyroidism With Offspring Neurodevelopment in TPOAb-Negative Women: A Prospective Cohort Study - Wang, Qingru; Jiang, Yangqian; Lv, Hong; Lu, Qun; Tao, Shiyao; Qin, Rui; Huang, Lei; Liu, Cong; Xu, Xin; Lv, Siyuan; Li, Mei; Li, Zhi; et al. (Frontiers in Endocrinology, 2022)
Objectives: Adequate maternal thyroid hormone availability is crucial for fetal neurodevelopment, but the role of maternal mild hypothyroidism is not clear. We aim to investigate the association of maternal mild hypothyroidism with neurodevelopment in infants at 1 year of age among TPOAb-negative women. Methods: The present study was conducted within the Jiangsu Birth Cohort. A total of 793 mother-infant pairs were eligible for the present study. Maternal thyroid function was assessed by measuring serum thyroid stimulating hormone, free thyroxine and thyroid peroxidase antibodies. Neurodevelopment of infants was assessed by using the Bayley Scales of Infant and Toddler Development third edition screening test (Bayley-Ⅲ screening test). Results: In the multivariate adjusted linear regression analyses, infants of women with subclinical hypothyroidism and isolated hypothyroxinemia were associated with decreased receptive communication scores (β = -0.68, P = 0.034) and decreased gross motor scores (β = -0.83, P = 0.008), respectively. Moreover, infants of women with high-normal TSH concentrations (3.0-4.0 mIU/L) and low FT4 concentrations were significantly associated with lower gross motor scores (β = -1.19, P = 0.032), while no differences were observed in infants when the mothers had a high-normal TSH concentration and normal FT4 levels. Conclusions: Maternal subclinical hypothyroidism is associated with decreased receptive communication scores in infants at 1 year of age. In addition, maternal TSH concentration greater than 4.0 mIU/L and maternal isolated hypothyroxinemia are associated with impaired gross motor ability of infants, especially in infants of women with high-normal TSH concentrations (3.0-4.0 mIU/L).